Pengaruh Nilai Perusahaan, Tingkat Utang, Dan Kesulitan Keuangan Terhadap Keputusan Hedging - Edon Ramdani; Putri Oktaviani (JURNAL AKUNTANSI BARELANG, 2021)
The purpose of this research is to investigate the influence of firm value, debt level, and financial distress on hedging decisions. The population of this research is the manufacturing company sector various industrial that listed in the Indonesia Stock Exchange (IDX) in 2015-2019. The sample used in this research consist of 12 manufacturing companies in the various industrial sector. The sampling method is non probability sampling with the sampling technique using purposive sampling. The analysis is performed by using regression analysis logistic. The results of the research with the logistic regression test show that in the LR test simultaneously all independent variables, namely Firm Value, Debt Level, and Financial Distress together have a effect on hedging decisions with a significant value less than 0.05, namely 0.004023 < 0,05. In the Z-score Test Statistic (partially), the Firm Value with a significant value of 0,0527 > 0.05, it does not affect the Hedging Decision. The Debt Level with a significant value of 0,0218 < 0.05 has effect on hedging decisions. Financial distress with a significant value of 0,0018 < 0.05, it has a significant effect on hedging decisions. The McFadden R2 test for the three variables obtained 16% while the remaining 84% was explained by other variables not explained in this research. Keywords: Firm Value, Debt Level, Financial Distress, Hedging Decisions.